Early- and longer-term outcomes of David versus Florida sleeve procedure: propensity-matched comparison. (28th February 2022) - Holubec, Tomas; Rashid, Hiwad; Hecker, Florian; Karimian-Tabrizi, Afsaneh; Miskovic, Alexandra; Hlavicka, Jan; Zacek, Pavel; Van Linden, Arnaud; Moritz, Anton; Walther, Thomas
Abstract: OBJECTIVES: The aim of this study was to compare short- and longer-term outcomes of David (DV) versus Florida sleeve (FS) procedure in patients requiring valve-sparing aortic root replacement. METHODS: Between January 1996 and December 2020 285 patients received a DV procedure (median age 60 years; 26% females) and 57 patients underwent an FS procedure (median age 64 years; 19% females) in our department. Propensity score matching using patient characteristics led to 58 (DV) versus 57 (FS) patients. End points were defined as primary: freedom from aortic valve and/or aortic root-related reoperation and freedom from aortic regurgitation ≥moderate and secondary: early and late survival. RESULTS: Thirty-day mortality was 2% (DV) and 0% (FS) ( P = 0.319). There was 1 early stroke in each group ( P = 0.990). Follow-up was complete in 99% with only 1 patient (FS) lost. The 5- and 10-year freedom from aortic valve and/or aortic root related reoperation was 98 ± 2% and 96 ± 3% in the DV group and 92 ± 5% and 84 ± 9% in the FS group, respectively ( P = 0.095). The 5- and 10-year freedom from aortic regurgitation ≥moderate was 88 ± 5% and 80 ± 8% in the DV group and 92 ± 5% and 78 ± 1% in the FS group, respectively ( P = 0.782). The 5- and 10-year survival rates were 93 ± 4% and 82 ± 6% (DV) vs 75 ± 7% and 67 ± 10% (FS), respectively ( P = 0.058). No case of endocarditis (DV) and 3 cases of endocarditis (FS) ( P = 0.055) were observed during follow-up. CONCLUSIONS: Both DV and FS resulted in similar early and longer-term outcomes with a trend to slightly better performance and survival in the DV group. Florida sleeve procedure might be an alternative approach for patients with higher-risk profiles requiring valve-sparing aortic root replacement. Abstract : In patients with aortic root aneurysm with or without concomitant aortic regurgitation (AR), very good long-term results have been reported for aortic root and valve replacement, as well as for valve-sparing aortic root replacement (VSARR) [1–5].